Perceptions of nurse professors about the intersection of assistantial and teaching work - Luiz Anildo Anacleto Silva; Éder Luís Arboit; Luís Antônio Müller; Monique Prestes; Indiara Sartori Dalmolin; Marcelo Machado Sassi (Universidade Federal de Santa Maria, 2014)
Doi: 10.5902/2179769210081 Aim: to understand the perceptions of nurse professors about the importance of healthcare experience regarding to the exercise of teaching. Method: The study is characterized as a descriptive exploratory study with a qualitative approach. In evaluating the data we used content analysis. Survey participants were seven university professors prior teaching practice had experience in assisting. Results: The study shows that the experience in the field of health care practice, contribute to the development of content, especially as regards to the intersection between theory and practice, Conclusion: The experience in assisting contributes with regard to education, to relate theory and practice, however, this is not evident in other activities such research an extension.